Model Bimbingan Islami Melalui Kegiatan Tahlilan Untuk Meningkatkan Religiusitas Masyarakat Desa Rowolaku - Supriyanto; Muhamad Rifa’i Subhi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Islamic guidance is a systematic effort to provide guidance and direction to individuals and groups in order to achieve happiness in this world and the hereafter, especially in matters of life. Among the approaches that are still relevant in the context of Islamic education to increase religiosity is through religious activities commonly carried out by the community, one of which is through tahlilan. The purpose of this study is to examine how Islamic guidance through tahlilan can have a positive impact, particularly in enhancing the religiosity of the community in Rowolaku village. Through interviews, observations, and documentation, it was found that Islamic guidance through tahlilan activities significantly increased the religiosity of the community, as evidenced by the increased level of community participation in tahlilan activities. Additionally, a spirit of mutual cooperation and solidarity among the community was also observed. Tahlilan, rooted in social group activities, has proven capable of inspiring positive activities in the spirit of worship. This study suggests further exploration and the use of more in-depth methods, such as quantitative approaches.